Making Education Spending Count for the Children of Autonomous Muslim Region of Mindanao : Public Expenditure and Institutional Review for ARMM Basic Education - Australia DFAT (World Bank, Washington, DC, 2015)
The project builds on support to DepEd ARMM through the Australian Aid Basic Education Assistance for Mindanao (BEAM) activity, and further initiatives by the World Bank and partners. Chapter two of this report proceeds with an introduction to ARMM’s development context, including the evolution of regional institutions and the basic education system. Chapter three describes the unique ARMM Public Expenditure Management ‘syndrome’ that contributes to the weaknesses analyzed in this report, and in turn informs its policy recommendations. Chapter four analyzes pub¬lic expenditures for basic education in terms of aggregate spending, expenditure composi¬tion, and specific challenges that the ARMM PEM syndrome poses for budgeting. Chapter five assesses budget execution and frontline delivery aspects of basic education resources, incorporating findings from the facilities survey. Chapter six summarizes the findings on public expenditure management for education in ARMM and derives recommendations both for reforms to ARMM institutions and for consideration by the transition commission and other stakeholders in the preparations for a new Bangsamoro political entity.